Karakteristik beton aspal lapisan pengikat (AC-BC) yang menggunakan bahan pengisi abu terbang batubara - M. Sa'dillah; Galih Damar Pandalu; Natalino Borromeu Martins (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
Coal consumption continues to increase resulting in waste in the form of rock ash (fly ash) is continuously increasing. Increased waste is a problem especially in polluting the environment. Therefore it is necessary to use coal waste. One way to utilize stone ash waste is to use it as a filler in binder-coated asphalt concrete (AC-BC). This study aims to determine the characteristics of binder-coated asphalt concrete (AC-BC) with varying grades of additivesfly ash tomarshall quotient. Parameters observed consisted of stability, melting (flow), air voids in the mix (VIM), voids filled with bitumen (VFA), voids between aggregates (VMA), andmarshall quotient (MQ). The results of the study can be concluded 1) the results of testing the binder layer concrete asphalt layer (AC-BC) showed that the optimal asphalt content was 5.57% with a stability weight of 1,103.48 kg,flow 3.17 mn, VIM 4.55%, VFA 78.48%, VMA 16.06% and weightmarshall quotient (MQ) 349.08 kg/mm; 2) The test results of the binder-coated asphalt concrete (AC-BC) showed that the optimum mixture was filler contentfly ash 4.19% with a stability weight of 925.65 kg,flow 3.67 mn, VIM 4.07%, VFA 77.23%, VMA 16.46% and weightmarshall quotient (MQ) 253.58 kg/mm.